PERANAN SITUS LIANG DALAM SISTEM PEMUKIMAN MASYARAKAT TORAJA - Rosmawati, Rosmawati (Universitas Hasanuddin, 2025)
Many scientific papers have been born to experts about the communities traditional Toraja settlements, but no one has discussed about how the role of burial (Liang) in Toraja settlement system. This paper described about Liang and role in human settlement systems Toraja, because in fact every Tongkonan (traditional house) have a partner, that is Liang. Liang Toraja communities regarded as banua tang merambu (no smoke rises from the chimney), which is considered by the Toraja people have the same value with Tongkonan, namely as a portion of their legacy and heritage for generations that is priceless.